New Fixation Method for Maxillary Distraction Osteogenesis Using Locking Attachments - Eduardo Yugo Suzuki (2018)
Purpose: The external traction hooks of the intraoral splint used in the rigid external distraction (RED) system for maxillary distraction osteogenesis interfere with the surgical procedures. The purpose of this study is to introduce an innovative splint fixation method for maxillary distraction osteogenesis with Locking Attachments and evaluate their advantages, such as reduction of operating time compared with the traditional intraoral splint method. Patients and Methods: Retrospective comparison of operative times of maxillary Le Fort I osteotomy procedures was carried out with the traditional protocol using the intraoral splint cemented to the maxillary dentition (n = 14), and a removable intraoral splint that is inserted postsurgically (n = 14). Operative procedure times were compared and analyzed statistically using the data extracted from the surgical records. Results: There were no complications inserting the removable splint postsurgically, including pain, discomfort, or time-consuming procedure. Stable and secure splint fixation was obtained before the distraction procedure and the desired treatment goals were obtained in all patients. The total operative procedure times were significantly reduced in the Locking Attachments group by 24% to 41% (approximately 65 minutes) compared with earlier operations involving the conventional splints (P < .05). Conclusions: Maxillary distraction osteogenesis with the Locking Attachments is a highly effective fixation approach to manage severe hypoplastic maxilla, eliminating lip constraints resulting from scarring and allowing for easier, more deliberate and careful dissection. The use of the Locking Attachments is reliable in craniofacial surgery and has proved to be advantageous in the reduction of the operating time and surgical risks. © 2006 American Association of Oral and Maxillofacial Surgeons.